Teknik Pembibitan Kopi (Coffea spp.) Berkualitas di UPTD BSPTH Dinas Kehutanan Provinsi Sumatera Barat - Suci Fadhillah Almeida; Abdul Razak (Lembaga Yasin AlSys, 2026)
Coffee seedling production (Coffea spp.) is an important stage in supporting successful productive and sustainable coffee cultivation. However, scientific documentation on coffee seedling production techniques in a comprehensive manner at regional seed institutions, particularly at the UPTD Center for Certification and Seedling of Forest Plants of the Forestry Office of West Sumatra Province, remains limited. This study aims to describe the stages of coffee seedling production, identify supporting factors for seedling production success, and explain the criteria for quality coffee seedlings ready to be distributed to the community. This study used a descriptive qualitative approach with a field study design. Data were collected through participatory observation, interviews with nursery officers selected purposively, field practice, and activity documentation. The data were analyzed descriptively through the stages of data reduction, data display, and conclusion drawing. The results showed that coffee seedling production was carried out through the stages of seed selection, soaking for 24 hours, sowing in a soil and burnt rice husk medium with a ratio of 3:1, transplanting at the soldier–spear phase, and maintenance in polybags. Germination success reached 85–90%, with seedlings ready for distribution at the age of 4–6 months, a height of 20–30 cm, and 4–6 pairs of healthy leaves. The conclusion of this study affirms that systematic coffee seedling production through seed selection, the use of appropriate planting media, and controlled maintenance can produce quality seedlings to support the development of coffee cultivation. The implications of this study provide practical contributions for regional seed institutions in strengthening technical standards for coffee seedling production and supporting the provision of quality seedlings for the community.